Outbreak analysis of meningococcal meningitis: A case series from a tertiary care hospital in Eastern India - Pratiksha Khatua,; Sumon Poddar,; Barnali Das,; Sumana Kundagrami,; Sumita Basu,; Rohit Kapoor,; Hriday De,; Ashok Modi,; Dinabondhu Sahana, (Asian Journal of Medical Sciences, 2024)
In a span of 4 months, there were 7 cases of meningococcal meningitis who presented with diagnostic dilemma and also a few atypical manifestations. A retrospective data analysis was carried out in children diagnosed with meningococcal meningitis who were admitted from October 2022 to January 2023. There were 7 confirmed cases of Neisseria meningitidis infections during the study period. The median age of presentation was 6 years (range: 4.5 months–9 years) with four males and three females. All the children presented with fever, but none had signs of meningeal irritation as such. Routine blood and cerebrospinal fluid (CSF) analysis were also near normal. Reverse transcriptase polymerase chain reaction (RT-PCR) for N. meningitidis was positive in the CSF samples of all the seven cases. All of the patients recovered completely, except that there were residues of neurodeficit in one patient. In endemic areas, pediatricians should have a low threshold of suspicion for N. meningitidis in children presenting with signs and symptoms involving the central nervous system and consider an RT-PCR of the CSF sample even if routine blood and CSF studies are near normal.